(untitled) (Global Journal of Science Frontier Research, 2025)
Currently, transformable rod systems are widely used in spacecraft panel designs and medicine in the form of various stands. It is of particular theoretical interest to develop the idea of geometric variability into spatial rod systems of complex shape. The concept of kinematic shaping of a regular rod system from a flat to a domed position is proposed. The finite element method in combination with the modified Lagrange method is used for numerical implementation. To assess the level of deformed state of a regular rod lattice, taking into account genetic nonlinearity, the values of longitudinal deformation in the rods are used.